Visibility, Credibility, Attraction dan Power Brand Ambassador Mempengaruhi Brand Image Produk Mie Sedaap Pada Mahasiswa - Annur Fitri Hayati; Noveline Patricia Damanik (Universitas Negeri Padang, 2022)
The purpose of this study was to determine the effect of visibility, credibility, attraction, power brand ambassador to brand Image of Mie Sedaap on students of the Faculty of Economics, Padang State University. This type of research is causative. The population in this study were students of the Faculty of Economics, Padang State University. The number of research samples based on William Cochran's formula was 97 people and selected using the Purposive Sampling technique. The data used is the type of primary data obtained through distributing questionnaires to students of the Faculty of Economics, Padang State University with predetermined criteria. The analytical method used is multiple regression analysis using SPSS 22. The results show that (1) Visibility, credibility, attraction and power of brand ambassadors together have a significant effect on Mie Sedaap's brand image in students of the Faculty of Economics, Padang State University with a value of 50.0% while the rest are other variables that were not investigated. (2) Visibility credibility, attraction and power of brand ambassadors each have a significant effect on Mie Sedaap's brand image on students of the Faculty of Economics, Padang State University. (3) Visibility brand ambassadors have the most influence. strong with a Beta value of 27.7% compared to the variables of credibility, attraction, power ambassador on the brand image of Mie Sedaap Products at the students of the Faculty of Economics, Padang State University.